2017
DOI: 10.1038/s41598-017-01940-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Bacillus subtilis strain 330-2 and its antagonistic genes identified by the removing PCR

Abstract: Plant growth-promoting bacteria (PGPB) may trigger tolerance against biotic/abiotic stresses and growth enhancement in plants. In this study, an endophytic bacterial strain from rapeseed was isolated to assess its role in enhancing plant growth and tolerance to abiotic stresses, as well as banded leaf and sheath blight disease in maize. Based on 16S rDNA and BIOLOG test analysis, the 330-2 strain was identified as Bacillus subtilis. The strain produced indole-3-acetic acid, siderophores, lytic enzymes and solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 85 publications
2
41
0
2
Order By: Relevance
“…So, microbial management of FS by utilizing endophytic Bacillus strains may offer a potential and viable solution to replace health hazardous and environmentpolluting chemicals. Endophytic B. amyloliquefaciens, B. subtilis, and B. cereus strains with antifungal activity towards diverse types of crop pathogens have been well documented [64][65][66][67]. The present investigation revealed that endophytic B. amyloliquefaciens (EPP35, EPP 42, EPP62, and EPP 102), B. subtilis subsp.…”
Section: Discussionmentioning
confidence: 67%
“…So, microbial management of FS by utilizing endophytic Bacillus strains may offer a potential and viable solution to replace health hazardous and environmentpolluting chemicals. Endophytic B. amyloliquefaciens, B. subtilis, and B. cereus strains with antifungal activity towards diverse types of crop pathogens have been well documented [64][65][66][67]. The present investigation revealed that endophytic B. amyloliquefaciens (EPP35, EPP 42, EPP62, and EPP 102), B. subtilis subsp.…”
Section: Discussionmentioning
confidence: 67%
“…Fusarium oxysporum f. sp. conglutinans ) ( Ahmad et al, 2017 ; Duijff et al, 1993 ; Sherriff and Lucas, 1990 ; Slusarenko and Schlaich, 2003 ; Sulochana et al, 2014 ). Applications of the H30-3 to the Chinese cabbage for disease management of downy mildew and Fusarium wilt remains investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Root exudates are composed of carboxylic acids, such as malate, citrate, and pyruvate, and vary across environments, specifically in response to the presence of phytotoxic compounds ( 2 ). Root exudates and released carboxylic acids also enable recruiting beneficial bacteria, such as the Gram-positive model bacterium Bacillus subtilis , that help to reduce susceptibility to plant pathogen attack ( 3 5 ). The assimilation of carboxylic acids by B. subtilis mainly relies on active transport systems, whose expression is induced via two-component systems (e.g., maeN by MalK/R [ 6 ]) by the transported carbon source ( 7 ).…”
Section: Introductionmentioning
confidence: 99%